Temple Bar as it appeared at the commencement of the 18th Century (Tufts Archival Research Center, 2005)
This illustration is from James Holbert Wilson "Temple Bar : the City Golgotha : a narrative of the historical occurrences of a criminal character associated with the present Bar"